2006
DOI: 10.1021/ie0511736
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Sorption-Enhanced Steam Reforming in a Dual Fluidized Bubbling Bed Reactor

Abstract: This paper highlights the use of a dual fluidized bed reactor system for producing hydrogen by sorption-enhanced steam methane reforming. Hydrogen concentrations of >98% are predicted for temperatures of ∼600 °C and a superficial gas velocity of 0.1 m/s, using a simple two-phase bubbling bed model for the reformer. The kinetics of the steam methane reforming and water-gas shift reactions are based on literature values, whereas experimentally derived carbonation kinetics are used for the carbonation of a dolomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 26 publications
2
86
0
Order By: Relevance
“…While the hydrogen molar fraction in gas phase increases only 0.415% (from 0.9881 to 0.9922) as the steam-to-carbon ratio increases from 4 to 5. The range of steam-to-carbon ratio from 3 to 4 is a better choice for SE-SMR process as proposed by Johnsen et al (2006b). After the steam-to-carbon ratio exceeds 4, the steam consumption will increase greatly with only a little increase of hydrogen production.…”
Section: Effects Of Steam-to-carbon Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…While the hydrogen molar fraction in gas phase increases only 0.415% (from 0.9881 to 0.9922) as the steam-to-carbon ratio increases from 4 to 5. The range of steam-to-carbon ratio from 3 to 4 is a better choice for SE-SMR process as proposed by Johnsen et al (2006b). After the steam-to-carbon ratio exceeds 4, the steam consumption will increase greatly with only a little increase of hydrogen production.…”
Section: Effects Of Steam-to-carbon Ratiomentioning
confidence: 99%
“…Prasad and Elnashaie (2004) proposed a circulating fluidized bed membrane reactor for SMR with CO 2 sequestration using the CO 2 -lime reaction and studied the reactor performance with a one-dimensional (1D) model. Johnsen et al (2006b) modeled the SE-SMR and sorbent regeneration processes conducted continuously in two coupled bubbling beds with a homogeneous model. Li and Cai (2007) made a simulation of multiple cycles for SE-SMR and sorbent regeneration in a fixed bed reactor.…”
Section: Introductionmentioning
confidence: 99%
“…A dual fluidized bed reactor is another important configuration that has advantage in terms of higher residence time for adsorbent and minimization of attrition of the adsorbent because of low gas velocities. Johnson et al 104 have carried out numerical investigations for this reactor configuration using a simple two-phase bubbling bed model and established that operation at relatively high-solid circulation rates gives higher system efficiency. The other recent studies include experimental and numerical investigations by Lee et al 105 and Ochoa-Fernandez et al 106 These models can be used for optimization and online control to achieve better performance.…”
Section: Sorption Enhanced Steam Methane Reformingmentioning
confidence: 99%
“…The removal of CO 2 shifts the thermodynamic equilibrium of the water gas shift (WGS) reaction to the hydrogen product. Using Ni as metal catalyst, good results have been reported in the sorption enhanced steam methane reforming [9][10][11][12] with hydrogen molar fractions higher than 95% and CH 4 almost completely reformed with an operative temperature that varied between 600 °C and 700 °C. In recent years several papers have reported gasification processes that include CO 2 capture with calcium oxide-based sorbents [13].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately these types of sorbents suffer from the conditions reached in both gasifier and combustion chamber, such as thermal stress and mechanical friction (especially in fluidized bed where bed material suffers of attrition problems). Many authors observed high decay in sorbent reactivity due to multiple CO 2 capture-regeneration cycles, accompanied by a significant decrease in porosity and surface area [10,11,25,26]. As a result, the literatures report many attempts to improve both reactivity and endurance of sorbents [9,13,27,28].…”
Section: Introductionmentioning
confidence: 99%